Make believe: police accountability, lying and anti-blackness in the inquest of Sean Rigg - Arthur, Carson Cole (Crime, media, culture, 2023)
In 2008, Sean Rigg, a 40-year-old Black British man died in England and Wales police custody. It was not until 4 years later at the inquest that it transpired one of the police officers involved, the custody sergeant, PS Paul White gave false information. White had claimed he saw Rigg in the van upon his arrival however CCTV footage demonstrated this did not happen. Following a deconstructive approach this paper examined the inquest transcripts to explore how belief and the possibility of being mistaken was integral to the account White provided. It is the ambiguity of truth/fiction that is significant in legal investigations for it comes to produce the justifications for the deaths of Black people in England and Wales.